The Organization of Negative Business Messages Preferred by Students in Higher Education - Wijayanti, Sri Hapsari (Asian Journal of Social and Humanities, 2023)
Written communication in an educational setting aims to convey messages related to academics or finances. The messages delivered contain either positive or negative information. This study aims to reveal the organization of negative business messages preferred by higher education students while receiving messages from university parties. The participants are the vice-chancellors for finance and academic affairs or the representatives (heads of divisions) at three private universities within the Association of Catholic Higher Learning Institutions as the senders and 170 active students in several universities as the receivers. This study uses quantitative and qualitative descriptive approaches. I collected data through online questionnaires, semistructured interviews, and observation of written documents in email and WhatsApp. I proposed four essential dimensions of negative message, namely, organization/approach, language, medium, and response, with the Likert scale questionnaire. I also inserted two cases of negative messages at the end of the questionnaire to find students’ tendency to select one they liked. The questionnaire results are used to discover the participants’ preference for the approach of relaying negative messages, corroborated by the interviews. The study found that students preferred direct approach to negative business messages. Buffers, prevalent in negative business with indirect order, are found in the email. A positive tone was not found at the end of the message. The study concluded that negative messages should be conveyed in writing with direct organizations and positive language and addressed to students before being forwarded to their parents